1998
DOI: 10.1063/1.122057
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characterization of GaN p-n junctions with and without threading dislocations

Abstract: The effect of dislocations on the electrical characteristics of GaN p-n junctions has been examined through current–voltage measurements. Lateral epitaxial overgrowth (LEO) was used to produce areas of low dislocation density in close proximity to areas with the high dislocation density typical for growth on sapphire. A comparison of p-n diodes fabricated in each region reveals that reverse-bias leakage current is reduced by three orders of magnitude on LEO GaN. Temperature-dependent measurements on the LEO di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
182
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 357 publications
(187 citation statements)
references
References 9 publications
5
182
0
Order By: Relevance
“…In contrast, from all tested structures only the smaller size mesas exhibit a noticeable increased resistance and nonlinear I-V characteristics. It decisively points to the detrimental role of highly conductive sapphire-GaN misfit-related threading dislocations [13], which short the insulating (Ga,Mn)N layer. The fact that the electrical characteristics of some of the 60 and 90 µm mesas are tunnel-like indicates that these highly conductive dislocations must be non-randomly distributed.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, from all tested structures only the smaller size mesas exhibit a noticeable increased resistance and nonlinear I-V characteristics. It decisively points to the detrimental role of highly conductive sapphire-GaN misfit-related threading dislocations [13], which short the insulating (Ga,Mn)N layer. The fact that the electrical characteristics of some of the 60 and 90 µm mesas are tunnel-like indicates that these highly conductive dislocations must be non-randomly distributed.…”
Section: Resultsmentioning
confidence: 99%
“…Kozodoy et al examined the effect of dislocations on the reverse bias current density by comparing the reverse bias current for p-n diodes on LEO GaN with that for diodes on the dislocated GaN, and found that reverse-bias leakage current was reduced by three orders of magnitude on LEO GaN. [23] Kuksenkov et al also showed that the dark current was correlated with dislocation density in GaN diodes. [24] However, scant information is available concerning the correlation between the high dislocation density and the electrical properties of ohmic contacts to p-GaN.…”
Section: Influence Of Micro-structural Defects On the Carrier Transportmentioning
confidence: 99%
“…Their influence on the electrical and optical properties of GaN and related alloys has been a subject of high interest. This includes their role as charged scattering centers and source of leakage paths in carrier transport in GaN materials and device structures [1,2]. Also, it has been suggested that radiative recombination processes such as the ubiquitous 2.2 eV ''yellow'' emission band occurs at or near dislocations [3].…”
Section: Introductionmentioning
confidence: 99%
“…1 Permanent Address: Physics Institute, Universidade de Brasilia, Brasilia, Brazil. 2 Current Address: Army Research Laboratory, Adelphi, MD 20783-1197 USA. 3 Current Address: Sandia National Laboratory, Albuquerque, NM 87185 USA.…”
Section: Introductionmentioning
confidence: 99%